Administrators’ Competencies and School Effectiveness in Osun State Secondary Schools - Adeseko Sunday Olaifa; Lateefah Bidemi Omisore-Abdulazeez; Moses Adeleke Adeoye; Oba Baba Ayoku; Ebunlomo Oreoluwa Olaifa (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
The role of school administrators in Nigeria and the appointment process are based on certain criteria considered by the Teaching Service Commission (TESCOM) under the supervision of the Ministry of Education. As key personnel in schools in Nigeria, the appointment of administrators has a significant impact on school management and overall quality of education. This study aimed to analyze the competence of administrators and the effectiveness of schools in Osun State secondary schools in three education districts in Osun State. This type of research is survey research with a descriptive research design. The population of the study amounted to 278 consisting of principals, vice principals, and department heads randomly selected in selected secondary schools in Osun State. The methods used to collect data are observations and questionnaires. The collected data were analyzed using the mean, standard deviation and movement correlation of Pearson products and the hypothesis was tested at a significance level of 0.05. The results showed that there was a significant relationship between administrator leadership competence, personnel competence, financial competence, communication competence, supervision competence and school effectiveness. An adequate national standard framework for school administrators is recommended in addition to qualifications, stages of education administrator training such as internships, educational sciences and annex tables for assignment arrangements. Administrators must be aware of the changes and innovations in educational administration in the 21st century in order for them to work effectively in carrying out their administrative duties.